EKSTRAKSI DAN KARAKTERISASI MINYAK DARI LIMBAH PADAT PABRIK MINYAK GORENG KELAPA SAWIT (Extraction and Characterization of Oil from Solid Waste of Palm Oil Refinery) - Nuryanto, Eka; Karo Karo, Justaman A.; Eddyanto, Eddyanto; Hasibuan, Hasrul Abdi (Baristand Industri Banda Aceh, 2016)
The most of solid waste from palm oil refinery is Spent Bleaching Earth (SBE) with amount of1.5-3.0 from Crude Palm Oil (CPO) are processed. Generally utilizing SBE is to landfills. This researchwill be extraction of oil from the SBE with reflux method using hexane and its characterization. In thisresearch, the variable is a comparison between SBE:hexane (w/v), i.e. 1:2, 1: 3, 1: 4, 1: 6 and 1: 8, andreflux temperature at room temperature, 50, and 70 Â°C. On the extraction of oil with reflux temperature50 oC at all comparison SBE:hexane (w/v), the amount of oil which is obtained under 31,11%. While mostoil is obtained at a reflux temperature of 70 oC with a comparison of SBE:hexane (1: 8 (w/v)) which reached34.58%. Characteristic of oil contains free fatty acids 33,62%, moisture content 6.6%, impuirities 2.8%,iodine number 40.5 mg I2/100 g, and the number of peroxides 104,92 meq O2/kg. The characteristics of thiskind of oil, cannot be categorized as CPO and edible oil. However it is still possible to be utilized as rawmaterial for the soap, grease, lubricants, biodiesel and other oleochemicals products.